Finite element analysis of hip implants with different lattice structures using additive manufacturing materials - Noman, Abdulla All; Mohd Shamil, Shaari; Mohd Akramin, Mohd Romlay (Universiti Malaysia Pahang, 2025)
A hip implant is surgically placed to replace damaged components and restore the patient’s mobility. Although hip implants are widely used, there is a need to improve their mechanical performance while minimizing weight. Traditional designs often compromise between strength and weight, which can lead to implant failure. This research presents the optimization of hip implant design to minimize weight while maintaining bio-mechanical strength under physiological loading conditions. The primary objective of this study is to investigate the mechanical behavior of hip implants using three different lattice structures for designing the lightweight hip implant. The results show that at 50% of the lattice level, the cubic lattice has the highest deformation of 0.13 mm, the triangle lattice has a similar deformation of 0.13 mm,while the hexagonal lattice has a lower deformation of 0.12 mm. The maximum equivalent stress of the cubic lattice is 363.7 MPa, and the triangle lattice is 364.82 MPa. Meanwhile, the hexagonal lattice has a lower value, at 280.97 MPa. All three lattice structures with 10%, 30%, and 50% lattice have different structural integrity, where the hexagonal lattice implant has the maximum level of stress distribution and structural integrity, particularly at higher lattice levels. Additionally, the cubic lattice minimizes 15.49% of mass, the triangular lattice minimizes 15.72% of mass, and the hexagonal lattice minimizes 15.84% of mass, which makes the hexagonal lattice ideal for hip implantsto achieve optimal mechanical performance and lightweight structure. In conclusion, the combination of finite element analysis and additive manufacturing can enhance the orthopaedicimplant design, especially for hip implants.